Diapositivos digitais móveis de comunicação e espaços públicos urbanos - Cleber Augusto Barreto Correa (2016)
This work deals with the relations between mobile digital communication devices and urban public spaces. The aim of this research is to analyze how the uses of mobile digital communication devices affect relations with urban public spaces. How they change the ways of living socially and as they tend to transform everyday spaces. The dissertation was developed through the production of drawings, photographic images and texts. The research came from observations of urban scenes, related to the object, which led to the production of drawings and photographs. The images were assessed considering the references. The result does not lead to a clear and objective answer about the objetc but takes the form of a mapping. The object is made explicit and reflections are pointed. Theres is a highlight on the need to look at the uses of mobile communication devices that foster better quality inter-subjective exchanges.